The consequences of health shocks on households: Evidence from China - Yajie Wang; Zhenjie Jin; Ye Yuan (China Economic Review, 2023)
Unexpected health shocks may bring catastrophic consequences for households. This paper examines the effect of unexpected adverse health shocks on household members' physical and mental health, labor supply, household income and asset, and health behaviors in China by analyzing two nationally representative datasets and adopting a difference-in-differences method augmented with coarsened exact matching. We find that an unexpected health shock results in a discounted out-of-pocket medical expenditure of 16,943 RMB (US$ 2647) over five years for an average household, a reduction of household income per capita of 841 RMB per year (US$ 131, or 6.0% of household annual income per capita), and a loss of net household asset per capita of 13,635 RMB (US$ 2130, or 9.7% of household asset per capita). It raises the probability of an average household applying for public poverty relief allowance by 2.8 percentage points. In addition, we document a strong intra-household spillover effect of health shocks on mental health and health behaviors. A simple back-of-envelope calculation shows that the health shock induces a private cost of 34,966 RMB (US$ 5463) over 5 years for an average household, and incurs a social financial burden of 6066 RMB (US$ 948) in 5 years per household in medical reimbursement and social welfare transfers. At a national scale, the total social burden of health shocks from cardiovascular and cerebrovascular diseases amounts to 1.1 trillion RMB (US$ 172.1 billion) over 5 years.